Pentingnya Pemahaman Integrasi-Interkoneksi dalam Upaya Deradikalisasi - Alfin Falah Fahrezy (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
This article attempts to dissect the roots of radicalism in Indonesia by using Amin Abdullah’s integration-interconnection analysis, which aims to formulate alternative solutions to deradicalization efforts. Judging from the phenomenon of radicalism so far, one-sided truth claims are one of the main causes of radicalism in addition to other factors such as economic and social. One-sided truth claims narrow the view in understanding religion and social reality. Moreover, the notion of radicalism also spreads in educational institutions and correctional institutions, which should be ideal places for deradicalization efforts. An integrative and interconnected paradigm directs a holistic mindset by paying attention to all fields of knowledge to help prevent partial and narrow product thinking. From this research, the integration-interconnection paradigm initiated by Amin Abdullah can be an ideal epistemological basis for preventing radicalism. Therefore, it becomes important to implement the integration-interconnection paradigm in the curriculum, both in educational and correctional institutions